2017
DOI: 10.1111/gbb.12438
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal nutrition interacts with genetic background to alter behavior in a parent‐of‐origin‐dependent manner in adult Collaborative Cross mice

Abstract: Previous studies in animal models and humans have shown that exposure to nutritional deficiencies in the perinatal period increases the risk of psychiatric disease. Less well understood is how such effects are modulated by the combination of genetic background and parent-of-origin (PO). To explore this, we exposed female mice from 20 Collaborative Cross (CC) strains to protein deficient, vitamin D deficient, methyl donor enriched or standard diet during the perinatal period. These CC females were then crossed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 92 publications
0
28
0
Order By: Relevance
“…The Collaborative Cross (CC) and its eight founder strains are an important resource for studying complex traits, establishing mouse models for human disease, and understanding the mouse Diversity Outbred (DO), which originated from the CC (Ferris et al 2013;Chesler 2014;Rogala et al 2014;Rasmussen et al 2014;Gralinski et al 2015Gralinski et al , 2017Schoenrock et al 2017;Maurizio et al 2018). The CC resource and its founder strains can also be used to study reproductive ability, which is especially interesting because this population has an established record both of breeding successes and of failures.…”
Section: Introductionmentioning
confidence: 99%
“…The Collaborative Cross (CC) and its eight founder strains are an important resource for studying complex traits, establishing mouse models for human disease, and understanding the mouse Diversity Outbred (DO), which originated from the CC (Ferris et al 2013;Chesler 2014;Rogala et al 2014;Rasmussen et al 2014;Gralinski et al 2015Gralinski et al , 2017Schoenrock et al 2017;Maurizio et al 2018). The CC resource and its founder strains can also be used to study reproductive ability, which is especially interesting because this population has an established record both of breeding successes and of failures.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, whole genome sequences have been established for each individual CC strain, and other genomic tools have been developed to enable the identification of genetic variants from mapping studies 9,10 . The CC has been used to model complex traits such as behavior [11][12][13][14] , cancer 15 , and infectious disease susceptibility [16][17][18][19][20][21][22][23] . In order for us to take advantage of the immense genetic diversity available in the CC to study epilepsy, we needed a seizure induction protocol amenable to high throughput analysis.…”
Section: Introductionmentioning
confidence: 99%
“…By mating different CC strains, we can generate recombinant inbred inter-crosses (CC-RIX) (Z ou et al . 2005; S choenrock et al . 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The genetic diversity of CC-RIX enables the study of parent-of-origin effects and their phenotypic characterization has demonstrated that there are strong strain effects in some measures (C rowley et al . 2015; S choenrock et al . 2018).…”
Section: Introductionmentioning
confidence: 99%